PENGEMBANGAN SISTEM BARTER OTOMATIS PADA APLIKASI CONTRACT FARMING DI PLANT FACTORY - , NATALIA A. TOMBOKAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Plant Factory (PF) is an environmentally controlled food production facility that releases the cultivation limit of the seasonal and climate conditions. By introducing contract farming system in PF, PF-customers (i.e. business owners namely restaurants and food retails) can rent spaces in PF and schedule the crop production. Moreover, an internal barter system is integrated to allow the exchange of crops scheduled by renters. In this research, a new system called Contract Farming in Plant Factory (CFPF) is proposed to accommodate the Farmto- Fork food supply along with accommodating the crop barter system. The CFPF system facilitates renters to rent spaces and conduct the crop barter by signing a contract with PF. In this research, a sorting mechanism is proposed to search for barter pairs based on the rentersâ farming schedules. The objective of the barter system is to minimize the value discrepancy of each barter pair. Four models with different barter constraints are investigated by developing an automatic barter framework using two algorithms, namely Hungarian Algorithm (HA) which integrates Hungarian method with the sorting mechanism and Heuristic Searching Algorithm (HSA). The simulation results suggest when PF tried to accommodate more diverse rentersâ preferences, HA generated more number of barter pairs, while HSA generated lower summation of value discrepancy providing fairer barter pairs. Another finding, the proposed automatic barter framework can enhance the crop diversity to the renters. In conclusion, the simulation results can be used to determine the implementation of barter mechanism when different barter contract designs of the CFPF are applied.